Enhancing Photoprotective Performance of Sunscreen Lip Tint Through Factorial Design Optimization of Naringenin and Titanium Dioxide - Eryani, Mikhania Christiningtyas; Azizah, Fatiya; Ameliana, Lidya; Sari, Lusia; Ryad Alati (Universitas Muhammadiyah Malang, 2026)
The sun emits various types of radiation, including ultraviolet (UV) radiation, which can damage skin structure, triggering premature aging, irritation, sunburn, and pigmentation disorders. Naringenin and titanium dioxide are known to have protective effects against UV radiation. This study aimed to evaluate the effects of naringenin and titanium dioxide concentrations and their interactions on the physical quality and in vitro sunscreen efficacy of lip tint formulations, and to determine the optimal formulation using Design-Expert software. This study is the first to optimize lip tint sunscreen using factorial design with naringenin and TiO₂.The results showed that the optimal formulation achieved an SPF of 38.23, %TE of 0.0562, and viscosity of 16,166 mPas at 2.1% naringenin and 10% titanium dioxide. Furthermore, higher concentrations of both active ingredients increased the SPF value and decreased the %TE and %TP values. Statistical analysis using a one-sample T-test showed no significant difference between the predicted and experimental results (p > 0.05), confirming the validity of the optimization model.